2010
DOI: 10.1016/j.molcel.2010.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Endonuclease Domain of MutL: Unlicensed to Cut

Abstract: Summary DNA mismatch repair corrects errors that have escaped polymerase proofreading, increasing replication fidelity 100- to 1000-fold in organisms ranging from bacteria to humans. The MutL protein plays a central role in mismatch repair by coordinating multiple protein-protein interactions that signal strand removal upon mismatch recognition by MutS. Here we report the crystal structure of the endonuclease domain of Bacillus subtilis MutL. The structure is organized in dimerization and regulatory subdomains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
234
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(250 citation statements)
references
References 30 publications
11
234
0
Order By: Relevance
“…Pillon et al (26) has shown that the regulatory subdomain of BsMutL CTD contains the ␤-clamp-interacting motif (␤ motif) as QEMIVP. They confirmed that the ␤ motif is responsible for the in vitro interaction with ␤-clamp and that mutation in the motif abolishes the MMR activity in vivo (26,38,42). To explain the enhancing effect of ␤-clamp interaction, an attractive model has been proposed in which a cluster of negatively charged residues in MutL CTD prevents the DNA binding and ␤-clamp neutralizes the negative charge to enable DNA binding (26).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 85%
See 1 more Smart Citation
“…Pillon et al (26) has shown that the regulatory subdomain of BsMutL CTD contains the ␤-clamp-interacting motif (␤ motif) as QEMIVP. They confirmed that the ␤ motif is responsible for the in vitro interaction with ␤-clamp and that mutation in the motif abolishes the MMR activity in vivo (26,38,42). To explain the enhancing effect of ␤-clamp interaction, an attractive model has been proposed in which a cluster of negatively charged residues in MutL CTD prevents the DNA binding and ␤-clamp neutralizes the negative charge to enable DNA binding (26).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 85%
“…Crystallographic analyses on the C-terminal domain (CTD) of eukaryotic and bacterial MutL endonuclease have shown that the domain is composed of regulatory and dimerization subdomains (11, 26 -28). The dimerization subdomain contains the metal-binding site essential for the endonuclease activity (29), in which two zinc ions are coordinated by the residues from highly conserved motifs: DQHAX 2 EX 4 E, ACR, and CPHGRP (11,15,26,30). These motifs are conserved in MutL from the majority of organisms except for limited species in ␥-proteobacteria (12, 15, 16, 19 -21, 31).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 99%
“…Many bacteria and all eukaryotes lack MutH (21). Instead, their MutL contains an endonuclease activity not present in E. coli MutL (22)(23)(24). The proposed mechanism of MMR requires a strand-specific signal to direct incision by MutL to the newly synthesized strand (22,25).…”
Section: Resultsmentioning
confidence: 99%
“…All eukaryotes, and most bacteria, lack methyl direction (i.e., they do not contain MutH or Dam methylase), instead containing a MutL with endonuclease activity. This report includes an examination of B. subtilis, a Grampositive bacterium that contains a MutL with endonuclease activity and does not use methyl direction for MMR (24). Even though B. subtilis MutL contains an intrinsic endonuclease activity, MMR requires a signal to specify MutL action to the newly replicated strand (22,25).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial MutS and MutL interact with the β-processivity clamp protein, suggesting they may associate with the replication fork (7)(8)(9). Earlier efforts by the Walker and Grossman laboratories (9,10) to localize MutS in live B. subtilis cells exploited a MutS-green fluorescent protein fusion (MutS-GFP).…”
mentioning
confidence: 99%